2014
DOI: 10.1080/09518398.2014.891772
|View full text |Cite
|
Sign up to set email alerts
|

Fostering intercultural understanding through secondary school experiences of cultural immersion

Abstract: In parallel with many nations' education policies, national education policies in Australia seek to foster students' intercultural understanding. Due to Australia's location in the Asia-Pacific region, the Australian government has focused on students becoming "Asia literate" to support Australia's economic and cultural engagement with Asian countries. Drawing on Allport's optimal contact principles and key factors supporting intercultural understanding, this study examines two "sister school" cultural immersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This assumption is not restricted to this school; it is reflective of attitudes of some stakeholders in Australia who maintain that Indigenous content is relevant only to Indigenous students, and to non-Indigenous students where there is significant overlap in the histories and cultures of Indigenous and non-Indigenous peoples (Australian Government 2014). It is also reflective of broader themes present in contemporary schooling, including reified, essentialised conceptions of 'culture' and 'Indigeneity' (Jayasuria 2008;Nakata, Nakata, Keech & Bolt 2012;Pinar 2011;Walton et al 2015). This view of the value of Aboriginal and Torres Strait Islander curriculum content can result in missed opportunities to engage with local content and knowledges.…”
Section: Adapting One Nation's Curriculum For Another Nation's Childrenmentioning
confidence: 99%
“…This assumption is not restricted to this school; it is reflective of attitudes of some stakeholders in Australia who maintain that Indigenous content is relevant only to Indigenous students, and to non-Indigenous students where there is significant overlap in the histories and cultures of Indigenous and non-Indigenous peoples (Australian Government 2014). It is also reflective of broader themes present in contemporary schooling, including reified, essentialised conceptions of 'culture' and 'Indigeneity' (Jayasuria 2008;Nakata, Nakata, Keech & Bolt 2012;Pinar 2011;Walton et al 2015). This view of the value of Aboriginal and Torres Strait Islander curriculum content can result in missed opportunities to engage with local content and knowledges.…”
Section: Adapting One Nation's Curriculum For Another Nation's Childrenmentioning
confidence: 99%
“…Engle & Engle (2004) reported college students demonstrated significantly higher levels of intercultural sensitivity after participating in a long-term study abroad program. Williams (2005) found college students who studied abroad demonstrated significantly higher levels of intercultural sensitivity than college students who remained on an American campus, and Walton et al (2015) found short cultural immersion experiences had a positive impact on high school students' levels of intercultural understanding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, two middle school students recently had an opportunity to travel to Benin, West Africa to complete a service-learning project and learn about musical and cultural traditions. Past researchers have reported short-term cultural immersion experiences and long-term study abroad programs made a positive impact on intercultural sensitivity at the secondary and university level (Engle & Engle, 2004;Walton et al, 2015;Williams, 2005). However, more research is needed to determine the specific benefits of short cultural immersion experiences at younger ages.…”
Section: Short-term Cultural Immersionmentioning
confidence: 99%
“…Australian studies of racism that take an anthropological perspective have explored Indigenous racism and anti-racism, multiculturalism, white paranoia, and colour blindness in the offline world (e.g. Cowlishaw 2000Cowlishaw , 2004Hage 2000Hage , 2014Kowal et al 2013;Kowal 2015;Walton et al 2014) but have not extended to the online world.…”
Section: Introductionmentioning
confidence: 99%